2007
DOI: 10.1002/cne.21513
|View full text |Cite
|
Sign up to set email alerts
|

Striatal projections of the vagal‐responsive region of the thalamic parafascicular nucleus in macaque monkeys

Abstract: We recently reported that the thalamic parafascicular nucleus (Pf) in monkeys is strongly activated by vagus nerve afferents. The main forebrain target of Pf is the striatum, but the specific striatal regions receiving visceral input via this pathway are unknown. We examined the projections of this region by injecting anterograde tracers into the vagus evoked potential (VEP) focus in Pf of macaque monkeys. The VEP was strongest lateral and anterior to the habenulointerpeduncular tract, but it was distributed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 99 publications
3
27
0
Order By: Relevance
“…This area had previously been assigned to S2. Similarly, the thalamocortical projections from gustatory and vagal-responsive neurons in VMb in the fundus of the anterior SLS (Pritchard et al, 1986;Ito and Craig, 2008) match exactly the mediolateral extent of the area that we identify as Idfa, which previously had been divided and labeled as various entities. The present observations provide the necessary architectonic foundation for the recognition of this entire longitudinal strip (Idfa 1 Idfp) as interoceptive cortex (see Craig, 2002Craig, , 2004Craig, , 2010.…”
Section: Utility Of This Map For the Analysis Of Insular Connectivitymentioning
confidence: 85%
See 1 more Smart Citation
“…This area had previously been assigned to S2. Similarly, the thalamocortical projections from gustatory and vagal-responsive neurons in VMb in the fundus of the anterior SLS (Pritchard et al, 1986;Ito and Craig, 2008) match exactly the mediolateral extent of the area that we identify as Idfa, which previously had been divided and labeled as various entities. The present observations provide the necessary architectonic foundation for the recognition of this entire longitudinal strip (Idfa 1 Idfp) as interoceptive cortex (see Craig, 2002Craig, , 2004Craig, , 2010.…”
Section: Utility Of This Map For the Analysis Of Insular Connectivitymentioning
confidence: 85%
“…1); however, we did not identify this as a distinct architectonic area because a border separating this from the medial portion of Idfa was often undistinguishable. (In addition, the available evidence indicates that the projection from VMb [or, VPMpc] straddles the fundus and occupies both walls of the anterior SLS, that is, the entire area Idfa, just like the projection from VMpo that straddles the posterior SLS and occupies the entire area Idfp (Pritchard et al, 1986;Ito and Craig, 2008;see Discussion).) Finally, there is often another apparent enlargement of Idfa anterior to the limen, but it is in fact due to the plane of section passing obliquely through the anterior closing of the SLS (see AP 21.6 in Fig.…”
Section: Granular Areasmentioning
confidence: 86%
“…Identification of the mechanism for the timing of sequential global emotional moments in the AIC is needed, because the present model does not specify how the endogenous time base is instantiated. The possibility that the strong influence of the heartbeat on the AIC and the dorsal putamen (Critchley et al 2004;Pollatos et al 2007;Ito & Craig 2008) might be important for the endogenous time base needs to be examined. The homeostatic model suggests that interoceptive feelings from the body provide the basis for the construct of the sentient self in global emotional moments, and so this model suggests potential explanations for the dependence of subjective time perception on interoceptive signals, such as body temperature (see Wittmann 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This convergence of evidence and model suggests that the same endogenous time base that is used to index the progression of global emotional moments is also used for subjective time estimation. If the strong heartbeat-related activation of the dorsal putamen (Ito & Craig 2008;Pollatos et al 2007) is used to index the shifting emotional moments in the AIC, for example, then the comparative buffer in the AIC could be used to compare the feeling associated with a prior time interval with the feeling of the present interval across the range of the metamemory, i.e. in the range of seconds to subseconds.…”
Section: Time Perception In the Homeostatic Model Of The Sentient Selfmentioning
confidence: 99%
“…The rationale of microburst stimulation is mainly based on the phenomenon of paired-pulse facilitation, meaning that two stimulations of a presynaptic terminal within a short period of time result in a larger evoked synaptic response to the second stimulation [45]. Hence, it has been shown that multiple stimulations of the vagus nerve within a short period of time evoked a larger response at central vagal targets [14,15]. Therefore, it can be expected that short bursts of stimulation of the vagus nerve ("microbursts") are more potent in affecting central mediators of VNS and could possibly be associated with a stronger antiepileptic effect compared to standard VNS.…”
Section: Discussionmentioning
confidence: 99%